2016
DOI: 10.1515/aiht-2016-67-2882
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex differences in genome damage between prepubertal and adult mice after exposure to ionising radiation

Abstract: The mechanisms that lead to sex and age differences in biological responses to exposure to ionising radiation and related health risks have still not been investigated to a satisfactory extent. The significance of sex hormones in the aetiology of radiogenic cancer types requires a better understanding of the mechanisms involved, especially during organism development. The aim of this study was to show age and sex differences in genome damage between prepubertal and adult mice after single exposure to gamma rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The most prominent example is HO‐1, in which male mice of both strains showed upregulation in either Day 1 or Day 2 whereas female mice did not (Figure ). A recent study investigated gender differences in genome damage in prepubertal and adult mice following 8 Gy gamma radiation using an in vivo micronucleus assay . Irradiation caused higher frequency of micronuclei in males of both age groups .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent example is HO‐1, in which male mice of both strains showed upregulation in either Day 1 or Day 2 whereas female mice did not (Figure ). A recent study investigated gender differences in genome damage in prepubertal and adult mice following 8 Gy gamma radiation using an in vivo micronucleus assay . Irradiation caused higher frequency of micronuclei in males of both age groups .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study investigated gender differences in genome damage in prepubertal and adult mice following 8 Gy gamma radiation using an in vivo micronucleus assay . Irradiation caused higher frequency of micronuclei in males of both age groups . Other studies have also shown that male mice sustained more radiation damage than female mice given the same exposure .…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have demonstrated a sex-difference in radiation-induced gene and protein expression, and global genome DNA methylation in male and female mice exposed to acute or chronic TBI ( Kovalchuk et al 2004 ; Kovalchuk et al 2004 ; Pogribny et al 2004 ; Silasi et al 2004 ). Also noted were altered microRNA expression patterns in irradiated hematopoietic or brain tissue ( Ilnytskyy et al 2008 ; Koturbash et al 2011 ), differential metabolites and cytokines ( Jones et al 2019 ), and rates of genome damage ( Stojkovic et al 2016 ). Using metabolomics, sex-differences were also reported in biomarkers from 7 Gy-irradiated NHPs ( Pannkuk et al 2015 ).…”
Section: Animal Selectionmentioning
confidence: 99%
“…It has been reported that both estrogen and testosterone may modify the organism’s response to irradiation. One study pointed out that such differences can occur pre-puberty [ 38 ].…”
Section: Resultsmentioning
confidence: 99%